Quality of life of teaching in Physical Education of Parana state, Brazil - Hudson de Resende Moreira; Juarez Vieira Nascimento; Christi Noriko Sonoo; Jorge Both (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to evaluate the correlation between the constructs of quality of work life (QWL) and lifestyle in Physical Education teachers from public schools in Parana State. The sample consisted of 654 teachers (299 men and 355 women), corresponding to a sampling error of 3.5%. A sociodemographic questionnaire, "Perceived Work Quality of Life Scale by Physical Education Teachers from Elementary to High School" and "Profile of Individual Lifestyle" were used for data collection. Statistical analysis was performed using the chi-square test and Spearman's correlation test. The results showed the dissatisfaction of teachers with wages, working conditions and balance between work and leisure. Most subjects presented positive lifestyle behaviors, but the components nutrition, physical activity and stress management were a matter of concern. Internal evaluation of QWL yielded higher correlation coefficients than lifestyle. When comparing the two analytical matrices, low levels of correlation were observed between components and overall assessment of the constructs.